FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI KERJA KARYAWAN PADA PT. PP LONDON SUMATRA INDONESIA, TBK MEDAN - Surbakti, Ariston; Tinambunan, Anita P (Jurnal Manajemen dan Bisnis, 2013)
The purpose of this study to determine the most dominant factor influencing employee motivation at PT. PP London Sumatra Indonesia Tbk Medan. The study population was all employees of PT. PP London Sumatra Indonesia Tbk Medan, which amounts to 220 people. Samples were taken as many as 69 people with stratified random sampling method. Required data collected through questionnaires. The data analysis technique used is the factor analysis. From the discussion Figures KMO Measure of Sampling Adeguacy (MSA) of 0.895 is above 0.50, with a significance of 0.000, then the variable deserves to be analyzed further. Scree plot showed a graph, where the first factor to factor 2 (component source line number = 1 to 2), the direction of the line declined sharply. Then from number 2 to number 4, the direction of the line is decreased with the smaller slope. Factor of four to twenty already under the number of the Y axis (eigenvalues). This indicates that the four factors most flattering to summarize the twentieth factors influencing employee motivation at PT. PP London Sumatra Indonesia Tbk Medan. The dominant factors influencing employee motivation at PT. PP London Sumatra Indonesia Tbk Medan is an award for his achievements with 0.830 correlation value, the status of the correlation values 0.808, 0.806 correlation value incentives and personal maturity with a correlation value of 0.804. Of the four factors, the most dominant influence employee motivation is reward high performance